A randomised trial deploying a simulation to investigate the impact of hospital discharge letters on patient care in general practice - Jiwa, Moyez; Meng, Xingqiong (Rosie); O'Shea, C.; Magin, P.; Dadich, A.; Pillai, V. (B M J Group, 2014)
Objective To determine how the timing and length of hospital discharge letters impact on the number of ongoing patient problems identified by general practitioners (GPs). Trial design GPs were randomised into four groups. Each viewed a video monologue of an actor-patient as he might present to his GP following a hospital admission with 10 problems. GPs were provided with a medical record as well as a long or short discharge letter, which was available when the video was viewed or 1 week later. GPs indicated if they would prescribe, refer or order tests for the patient's problems. Methods Setting Primary care. Participants Practising Australian GPs. Intervention A short or long hospital discharge letter enumerating patient problems. Outcome measure Number of ongoing patient problems out of 10 identified for management by the GPs. Randomisation 1:1 randomisation. Blinding (masking) Single-blind. Results Numbers randomised 59 GPs. Recruitment GPs were recruited from a network of 102 GPs across Australia. Numbers analysed 59 GPs. Outcome GPs who received the long letter immediately were more satisfied with this information (p<0.001). Those who received the letter immediately identified significantly more health problems (p=0.001). GPs who received a short, delayed discharge letter were less satisfied than those who received a longer delayed letter (p=0.03); however, both groups who received the delayed letter identified a similar number of health problems. GPs who were older, who practised in an inner regional area or who offered more patient sessions per week identified fewer health problems (p values <0.01, <0.05 and <0.05, respectively). Harms Nil. Conclusions Receiving information during patient consultation, as well as GP characteristics, influences the number of patient problems addressed. Trial registration number ACTRN12614000403639.